Effect of prepartum supplementary feeding of urea molasses multi-nutrient block on post-partum production and fertility in dairy buffaloes - Brar, P S; Nanda, A S (The Indian Journal of Animal Sciences, 2007)
Excessive drainage of body reserves in immediate post-partum period leads to excessive body weight loss and poor post-partum reproduction. Effect of supplementary feeding of urea molasses multi-nutrient blocks (UMMB) to 15 prepartum Murrah buffaloes on their post-partum reproduction performance was assessed. Supplementary feeding of UMMB prepared by 'cold process' using locally available agro-industrial byproducts was started 60 days before the expected date of calving up to the day of calving. Observations on body weight, body condition score (BCS), heart girth, milk yield and estrus and ovarian activity were made up to 60 days post-partum. The average daily intake of UMMB per animal per day was 674 g. The body weight and BCS gains during prepartum period were more in the supplemented buffaloes than in un-supplemented buffaloes. UMMB supplemented buffaloes lost less weight as compared to un-supplemented buffaloes during early post-partum period. Average daily milk production was higher (9.65±0.48 vs 8.16±0.56 kg during first 60 days post-partum) and days to first ovulatory oestrus were less in supplemented buffaloes (34 vs 48 days) than in un-supplemented controls. The quality of oestrus, in terms of symptoms and nature of mucus, in terms of transparency and string formation were better in the supplemented buffaloes Overall UMMB supplementation during prepartum period improved post-partum production and reproduction in dairy buffaloes.